Perception of business actors toward the transition from LPPOM-MUI to BPJPH in halal certification governance - Purwanto, Endi Hari; Anggundari, Widia Citra (IPB University, 2025)
The enforcement of the mandatory halal certification policy by the Government became effective from October17, 2019. However, proper implementation requires thorough evaluation to understand how business actorsrespond to and use services previously provided by Halal Certification Institution. Therefore, this study aims toexamine the effectiveness of the institution in delivering advisory services, level of competence, and the extentto which the associated costs motivate business to pursue certification in accordance with the quality of servicesprovided. The three aspects provide valuable advice for the next designated authority to emulate the performanceexperience. The survey method was used, and the samples comprised 91 individuals from large, medium, andsmall business across 11 provincial cities in Indonesia. The field survey data were analyzed using descriptivestatistics with justification. The results showed that 81.4% of business expressed satisfaction with the performanceof the halal certification body, 80.3% recognized the institution commitment to service quality, and 59.4% supportedthe certification requirements.